Exploration of Emotion Regulation Experiences in an Emerging Adult with a Background of Emotional Abuse - Dien Amrina Rasyada; Mimbar Oktaviana (International Conference on Psychology and Education (ICPE), 2025)
This study presents a phenomenological exploration of emotion regulation in an emerging adult female with a background of childhood emotional abuse. The research analyzes data obtained through in-depth interviews, observational notes, and supporting anamnestic narratives from both the participant and a close friend. The analysis reveals five dominant emotion regulation patterns: emotional suppression, avoidance and withdrawal, difficulty with reframing, physical symptoms as expression, and over-functioning as avoidance. These findings illustrate how early psychological invalidation impacts the development of maladaptive regulation strategies, influencing the participant’s present coping behaviors, self-perception, and interpersonal functioning. The study highlights how safe, supportive relationships may foster more adaptive emotional functioning in adulthood. The findings contribute to the understanding of trauma-informed care for emerging adults and offer insights for psychologists, educators, and caregivers supporting individuals with similar developmental backgrounds.